Photo scrapbook page (1958)
Series of photographs of Alice E Harris, James C Bowers, and unidentified individuals. Includes a photo postcard of Sister's Inn with text "Protect your California Business Elect Thomas F. Nolan State Senator." The photo in the bottom right corner is of Ida Spencer (center foreground) and Alice Joyce, Annazette Williams, and Rosa Lee Williams. The Sister's Inn was located on the corner of Higuera Street and South Street and was a Black-owned restaurant in San Luis Obispo.